The Effect Of Profitability, Capital Intensity, and Leverage On Tax Avoidance: Evidence From Indonesian Property and Real Estate Companies (2019–2022) - Erlynda Yuniarti Kasim; Fira Sri Rahayu (International Journal of Management and Business Economics, 2026)
Tax is the primary source of government revenue and plays a crucial role in financing national development and public services. However, efforts to optimize tax revenue continue to face challenges due to corporate tax avoidance practices. The property and real estate sector is particularly relevant for examining tax avoidance because it is characterized by substantial fixed asset ownership, intensive capital investment, and diverse financing structures, which may create opportunities for tax planning strategies. This study aims to analyze the effects of profitability, capital intensity, and leverage on tax avoidance among property and real estate companies listed on the Indonesia Stock Exchange during the 2019–2022 period. This study employs a quantitative approach with an explanatory research design. Secondary data were obtained from companies’ annual financial statements. Using purposive sampling, 14 companies were selected, resulting in 56 firm-year observations. Profitability was measured using Return on Assets (ROA), capital intensity was measured by the ratio of fixed assets to total assets, leverage was measured using the Debt-to-Equity Ratio (DER), and tax avoidance was proxied by the Cash Effective Tax Rate (CETR). The data were analyzed using panel data regression with EViews 12 software. The results show that profitability has a positive and significant effect on tax avoidance, indicating that more profitable firms tend to engage in greater tax avoidance activities. Leverage also has a positive and significant effect on tax avoidance, suggesting that firms with higher debt levels are more likely to utilize tax-saving strategies. In contrast, capital intensity does not have a significant effect on tax avoidance. Simultaneously, profitability, capital intensity, and leverage significantly influence tax avoidance. This study contributes to the tax avoidance literature by providing empirical evidence from the Indonesian property and real estate sector, highlighting the importance of profitability and financing decisions in shaping corporate tax avoidance behavior. The findings offer insights for policymakers, regulators, and investors in understanding the determinants of tax avoidance in asset-intensive industries.